Analysis of the Hydrological Regime in Small Basins within the Three Gorges Reservoir Area During the Impoundment Period - YIN Siwei; HU Huiling; WANG Yuefeng; LEI Chaogui (Renmin Zhujiang)
Hydrological regime is an important problem brought about by the Three Gorges Project and directly influences the development and utilization of water resources and ecological sustainable development in the Three Gorges Reservoir Area.Existing studies mainly focus on the influence of water storage on the main stream of the Yangtze River,with little attention to the runoff variations in small basins of the reservoir area.Based on the daily hydrological data of three typical small basins (Daning River,Pengxi River,and Modaoxi River) in this area from 2003 to 2017,by adopting the methods of trend analysis,runoff concentration degree, and runoff concentration period,the multi-time scale change characteristics of runoff are identified from the aspects of runoff and dispersion degree.Meanwhile,the runoff characteristics before and after 175 m water storage (2003—2008,2009—2017) are revealed,and the influencing factors of runoff variations are discussed.The results are as follows.① The average annual runoff of the Daning River Basin and Pengxi River Basin shows a downward trend,but there are no obvious variations in the Modaoxi River Basin.The monthly average runoff in the three basins varies greatly.The runoff of the Daning River Basin and Pengxi River Basin has a significant decrease in the flood season (July),while that of the Modaoxi River Basin has significant increases in the non-flood season (February),and the extreme value of runoff mainly shows a non-significant downward trend.② The runoff concentration degree and runoff concentration period of each basin show a non-significant decrease or increase respectively.③ After water storage,the runoff concentration period of each basin obviously lags behind the precipitation,the annual runoff distribution tended to be uniform,and the precipitation-runoff correlation decreases.The correlation coefficient of monthly average runoff decreases about 2%~6%,while that of annual extreme value decreases about 3%~12%.The research results can provide a scientific basis for hydrological and water resources management in small basins in the Three Gorges Reservoir Area.